Resonant photoproduction of e⁺e⁻-pair with photon emission in strong magnetic field - Fomin, P.I.; Kholodov, R.I. (Вопросы атомной науки и техники, 2007)
The quantum-electrodynamic process of electron-positron pair production by a photon is considered in a strong external magnetic field. The process is accompanied by emission of the final photon. Kinematics and resonance conditions are found in ultraquantum approximation, namely the approximation of the strong magnetic field and low-excited states of an electron and a positron. The resonance conditions are realized, if the energy of the final photon equals to the distance between the Landau levels of an electron. A probability of the resonance electron-positron pair production with photon emission is found in the form of the Breit-Wigner cross section. This value is comparable with the probability of e⁺e⁻-pair production without photon emission. Розглядається квантово-електродинамічний процес народження електрон-позитронної пари фотоном в сильному зовнішньому магнітному полі. Процес супроводжується випромінюванням кінцевого фотона. Знайдено кінематику і резонансні умови в ультраквантовому наближенні, наближенні сильного магнітного поля і слабо збуджених станів електрона і позитрона. Резонансні умови реалізуються, якщо енергія кінцевого фотона дорівнює відстані між рівнями Ландау електрона. Імовірність резонансного народження електрон-позитронної пари з фотонною емісією здобута у формі перерізу Брейта-Вігнера. Ця величина одного порядку з імовірністю народження e⁺e⁻-пари без випромінювання фотона. Рассматривается квантово-электродинамический процесс рождения электрон-позитронной пары фотоном в сильном внешнем магнитном поле. Процесс сопровождается испусканием конечного фотона. Найдены кинематика и резонансные условия в ультраквантовом приближении, приближении сильного магнитного поля и слабо возбужденных состояний электрона и позитрона. Резонансные условия реализуются, если энергия конечного фотона равна расстоянию между уровнями Ландау электрона. Вероятность резонансного рождения электрон-позитронной пары с фотонной эмиссией получена в форме сечения Брейта-Вигнера. Эта величина одного порядка с вероятностью рождения e⁺e⁻-пары без излучения фотона.